Mesto, rol' i perspektivy federtsii v razvitii sporta - Sukhanov, A. D. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
About the place, role and perspectives (actual and historical) of the national sport federations in development of sport in Russia.